Realistic but not pessimistic: Finnish translation students’ perceptions of translator status - Ruokonen, Minna (The Journal of Specialised Translation, 2016)
Research on translator status, or prestige, has only been studied empirically within the last decade and mainly from the perspective of professional translators. Less attention has been paid to future translators: translation students. This article explores Finnish translation students' perceptions of translator status and its parameters, discussing implications for the future of the profession. The data consist of 277 responses from five universities, collected in 2013–2014 by an electronic survey adapted from Dam and Zethsen's translator questionnaires. Quantitative analyses indicate that the students' perceptions are partly very similar to professional translators': they rank translator status as middling or low and believe that translators' expertise is insufficiently recognised outside the profession. On the other hand, the respondents also perceive translators' influence as higher than in previous research. The study also illustrates the complexity of translatorial (in)visibility and power. On the whole, while aware of problematic aspects of the profession, the respondents are fairly committed to their field and confident that translators can influence their working conditions and translator status, a combination that seems promising for the future of the profession.